2003
DOI: 10.1109/jsen.2003.818459
|View full text |Cite
|
Sign up to set email alerts
|

Micro-electro-discharge machining as microsensor fabrication technology

Abstract: This paper presents the design and fabrication of three miniaturized mechanical sensors to demonstrate the three-dimensional machining capabilities of micro-electro-discharge machining (EDM). The first sensor is an inertial bi-axial inclination sensor. The displacement of an inertial mass is measured optically by means of a two-dimensional position sensitive device (PSD). The machining freedom of micro-EDM makes it possible to produce both sensor and housing in one monolithic structure. The second sensor is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…For the spider-spring, we focus on two different manufacturing techniques (Electro Discharge Machining [14,15] -EDM -and SU8 lithography [16,17]) implying two different materials. The EDM milling procedure was chosen as it was one of the few mechanical manufacturing possibilities to realize the interior cuttings.…”
Section: Valve Manufacturingmentioning
confidence: 99%
“…For the spider-spring, we focus on two different manufacturing techniques (Electro Discharge Machining [14,15] -EDM -and SU8 lithography [16,17]) implying two different materials. The EDM milling procedure was chosen as it was one of the few mechanical manufacturing possibilities to realize the interior cuttings.…”
Section: Valve Manufacturingmentioning
confidence: 99%
“…The more recent trends have shown that the drive has gone beyond the earlier challenge of precision and minuteness in dimension to a new level where components of the same precision and invisible dimensions are demanded to be machined on tough materials with lower cost. Semiconductor processing technologies such as photolithography on a silicon substrate are used for fabricating MEMS components (5,6). The material properties of silicon often do not meet the requirement of recent applications of these microparts because they require high-quality structure and capability to withstand high strength.…”
Section: Introductionmentioning
confidence: 99%
“…Micro metallic machine components have important applications in the watch-making industry [2], instrumentation and medical devices [3] and the related fabrication technology has been widely studied. Micro-electro-discharge machining (micro EDM) is one of the fabrication techniques in which different types of miniature components are fabricated [4,5]. EDM is limited to the fabrication of conductive materials.…”
Section: Introductionmentioning
confidence: 99%